Implementation Acupressure on the Taichong Acupoint in Lowering Blood Pressure in Patients with Hypertension stage 2 and 3 in Emergency Room RSUD dr. R. Goeteng Taroenadibrata Purbalingga: A Case Study - Diana Maf’ulah; Sidik Awaludin; Galih Noor Alivian; Catur Desi N (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
Background. Nowadays the prevalence of hypertension is more increasing. During this time the management of hypertension only uses pharmacological therapy, so it can cause complications. Therefore they need non-pharmacological therapy. One of the non-pharmacological therapy is acupressure on the Taichong acupoint. This aim of the implementation is to evaluate the effectiveness of accupressure on the Taichong acupoint in lowering blood pressure in patients with hypertension. Methods. The method used is a case study. Twelve patients with hypertension stage 2 and 3 at the emergency room RSUD dr. R. Goeteng Taroenadibrata Purbalingga be respondents of the implementation. Acupressure was applied to the Taichong acupoint for 3 minutes. Blood pressure was measured by digital sphygmomanometer before, immediately, and 15 minute after acupressure. Results. The results of the implementation showed that blood pressure before and after acupressure on the Taichong acupoint had a systolic decrease of 5-33 mmHg and a diastolic decrease of 3-18 mmHg. Conclusion. Acupressure on the Taichong acupoint can lowering blood pressure in hypertensive patients and may be included in the nursing care plan for hypertension.